Homozygous Mutations in GDAP1 and MFN2 Genes Resulted in Autosomal Recessive Forms of Charcot-Marie-Tooth Disease in Consanguineous Pakistani Families - Asif, Muhammad; Chiou, Chien-Chun; Hussain, Malik Fiaz; Hussain, Manzoor; Sajid, Zureesha; Gulsher, Muhammad; Raheem, Afifa; Khan, Adil; Nasreen, Nasreen; Kloczkowski, Andrzej; Hassan, Mubashir; Iqbal, Furhan; et al. (DNA and cell biology, 2023)
Charcot-Marie-Tooth disease (CMT) is a heritable neurodegenerative disease of peripheral nervous system diseases in which more than 100 genes and their mutations are associated. Two consanguineous families Dera Ghazi Khan (PAK-CMT1-DG KHAN) and Layyah (PAK-CMT2-LAYYAH) with multiple CMT-affected subjects were enrolled from Punjab province in Pakistan. Basic epidemiological data were collected for the subjects. Nerve conduction study (NCS) and electromyography (EMG) were performed for the patients. Whole-exome sequencing (WES) followed by Sanger sequencing was applied to report the genetic basic of CMT. The NCS findings revealed that sensory and motor nerve conduction velocities for both families were <38 m/s. EMG presented denervation, neuropathic motor unit potential, and reduced interference pattern of peripheral nerves. WES identified that a novel nonsense mutation (c. 226 G>T) in gene and a previously known missense mutation in gene (c. 334 G>A) cause CMT4A (Charcot-Marie-Tooth disease type 4A) in the PAK-CMT1-DG KHAN family and CMT2A (Charcot-Marie-Tooth disease type 2A) in the PAK-CMT2-LAYYAH family, respectively. Mutations followed Mendelian pattern with autosomal recessive mode of inheritance. Multiple sequence alignment by Clustal Omega indicated that mutation-containing domain in both genes is highly conserved, and analysis revealed that both mutations are likely to be pathogenic. We reported that a novel nonsense mutation and a previously known missense mutation in gene and gene, respectively, cause CMT in consanguineous Pakistani families.